Culture and the natural environment. (April 2016) - Milfont, Taciano L; Schultz, P Wesley
Highlights: The way individuals relate to the natural environment is culturally patterned. The article reviews cultural differences and similarities in human–nature relations. Future thinking, altruism, and psychological distance are possible universals. Cultural variations in human-centered reasoning and environmentalism also noted. New analyses of cross-cultural data involving 78 countries are reported. Abstract : The way individuals relate to the natural environment is culturally patterned. In this article we review and discuss cross-cultural differences and similarities in a number of important domains including environmental concern, environmental risk perception, and pro-environmental behaviour. Three possible psychological universals (future thinking, self-transcendent orientation, and psychological distance) in association with pro-environmental attitudes and behaviour are proposed, and cultural variations are also discussed. We highlight evidence — including new analyses of cross-cultural data — indicating that an overwhelming majority of the world's population supports environmental protection, and identifies with the value of 'looking after the environment.'